Psychometric approach of the revised illness perception questionnaire for oral health (IPQ-R-OH) in patients with periodontal disease (2019)
Background: The purpose of this study was to evaluate the psychometric properties of the validated Spanish version of the Illness Perception Questionnaire Revised for Oral Health (IPQ-R-OH) in patients with periodontal disease. Methods: We used the IPQ-R-OH, a 36-item self-report scale. This study was carried out using data from 517 patients with periodontal disease attending the dental clinic at the Universidad Cooperativa de Colombia, Pasto, Colombia. A three-parameter logistic model (3PL) for polytomous response was calculated to evaluate a model of individuals' responses. The McDonald's Omega (O = 0.60) coefficient and composite reliability were used to determine the internal consistency. Confirmatory factor analysis (CFA) was conducted to examine the fit of the hypothesized seven-factor model, and the configural invariance was tested to estimate the structure in each sex group. Results: The slope, location, and guessing parameters determined reasonable accurate items according to item response theory analysis. The internal consistency coefficients of each factor ranged from 0.62 to 0.93 (McDonald's Omega) and 0.66 to 0.87 (composite reliability). Confirmatory factor analysis indicated a seven-factor model (? 2 S-B  = 2572.165; ? 2 S-B /(573) = 4.489, P < 0.01; non-normed fit index = 0.950; CFI = 0.950; root means square error of approximation = 0.055 (90% confidence interval [0.052 – 0.059]); standardized root mean residual = 0.080 and Akaike information criteria = 1426.165. The seven factors loaded similarly to the original IPQ-R scale. Multigroup CFA analysis results supported factor invariance across the sex groups. Conclusion: These findings suggest that the IPQ-R-OH has adequate reliability and construct factorial validity; therefore, it could be a valuable instrument in screening illness perceptions in patients with periodontal disease. © 2018 American Academy of Periodontology